Innovation strategies for development and resilience of medium-size cities - Méndez Gutiérrez del Valle, Ricardo (Documents d’Anàlisi Geogràfica, 2013)
Cities of our area are faced with a raising competition from globalization, as well as with the impact of a systemic crisis that questions some previous growth models. Along with the aim of increasing the effort of economic and social innovation, is important now to use these strategies to overcome the shrinkage of some cities. Although most studies on innovation, knowledge or creativity have been focused on large cities and metropolitan areas, the medium-sized cities shows a growing interest, both from the perspective on territorial cohesion as to provide recent examples of cities that have surpassed decline processes through innovative strategies. This paper provides a theoretical reflection on the concepts of innovative city and urban resilience, identifies its main features, presents the keys factors to explain the uneven paths of medium-sized cities and propose policies to promote urban innovation.